Studi Pemanfaatan Abu Ampas Tebu Sebagai Substitusi Parsial Semen Pada Campuran Bahan Pembentuk Mortar Untuk Pekerjaan Sipil - Hakim, Abdul (Jurnal Serambi Engineering, 2025)
Some waste has the potential to cause pollution, but there is waste that is useful as a mortar mixture, namely sugar cane bagasse ash (AAT). This study aims to determine the chemical composition of SBA and its suitability as a material for reducing cement content in the mortar formation process. Laboratory tests, including chemical composition tests, XRD, and SEM, were conducted to determine the morphological structure of SBA and mortar. Additionally, physical tests were conducted on the mortar-forming materials to verify whether they met the standards. Furthermore, mortar samples with SBA content of 0%, 5%, 10%, 15%, 20%, and 25% SBA content, with dimensions of 5x5x5 cm³, were prepared for compressive strength testing at 7, 14, and 28 days, and with a diameter of 7.5 cm and length of 15 cm for splitting tensile strength and water absorption testing at 28 days. Tensile strength and water absorption tests were conducted at 28 days. The compressive strength test results showed that mortar with 5% SBA content had the highest compressive strength and split tensile strength at 28 days, specifically 22.26 MPa and 4.48 MPa, representing increases of 29.02% and 13.71% from mortar with 0% SBA. Meanwhile, the results of the water absorption test showed that the 5% SBA mortar had the lowest water absorption rate, which was 8.59%.